Dimercaprol (BAL): Insights into conformational stability, fragmentation pathways via tandem LR-ESI, HR-EI mass spectrometry, and gas-phase thermochemical properties from quantum chemical calculations - Miguel Fernando Molano; Alba Marcela Gómez Gómez; Alejandro Moncayo-Lasso; Carlos A. Bejarano; John Edward Diaz; Cristian Buendía-Atencio; Miguel Ángel Delgado; Vaneza Paola Lorett Velásquez; Alix E. Loaiza; Sol M. Mejía (PLoS ONE, 2026)
Dimercaprol (British antilewisite, BAL) is a long-established chelating agent used in the treatment of heavy metal poisoning; however, its physicochemical and thermochemical properties have not yet been fully characterized. In this study, we combined gas-phase quantum chemical calculations with high-resolution mass spectrometry to investigate the conformational stability, fragmentation pathways, and thermochemical parameters of BAL. Fragmentation behavior was examined by gas chromatography/mass spectrometry-QTOF under electronic ionization conditions, and the resulting spectra were interpreted through proposed dissociation pathways involving water, hydrogen sulfide, and thiyl radical losses, supported by reaction enthalpies calculated at the theoretical level M06-2X/6–311++G( 3df,3pd ). Conformational analysis identified five low-energy structures (BAL-1 to BAL-5), where intramolecular hydrogen bonds and gauche/anti interactions play a key role in stability; BAL-3 was consistently predicted as the lowest-energy conformer. Vibrational frequencies calculated with the B3LYP, M06-2X, and MN15 functionals showed good agreement with experimental FTIR and Raman data. The thermochemical properties were further evaluated using G n composite methods (G3MP2B3, G3B3, G4MP2 and G4) which yielded an average standard enthalpy of formation at ΔH° ( f,298K ) of –45.6 ± 1.1 kcal/mol. This work provides a detailed experimental and theoretical characterization of dimercaprol, providing information on its possible fragmentation mechanism and conformational landscape, and offering a thermochemical framework that could support future pharmacological, toxicological and environmental applications.